Globally Harmonized System of Classification and Labelling of Chemicals (GHS) - United Nations (United Nations, 2010)
The GHS addresses classification of chemicals by types of hazard and proposes harmonized hazard communication elements, including labels and safety data sheets. It aims at ensuring that information on physical hazards and toxicity from chemicals be available in order to enhance the protection of human health and the environment during the handling, transport and use of these chemicals. The GHS also provides a basis for harmonization of rules and regulations on chemicals at national, regional and worldwide level, an important factor also for trade facilitation. This edition contains new and revised provisions concerning, inter alia, the allocation of hazard statements and the labelling of small packagings, two new sub-categories for respiratory and skin sensitization, the revision of the classification criteria for long-term hazards to the aquatic environment, and a new hazard class for substances and mixtures hazardous to the ozone layer.